MARMARA DEPREMİNDE ÖĞRENCİLERDE OLUŞAN ANKSİYETE İLE İLİŞKİLİ ETKENLER - ERTEM VEHİT, Hayriye and PEYKERLİ, Gülcan and TOPARLAK, Derya and ALYANAK, Behiye (Cerrahpaşa Medical Journal, 2014)
Background and Design.- This research is based on the assumption that the 17th August Marmara Earthquake affected male students more than the female students. Spielberger State-Trait Anxiety Inventory and a developed questionnaire were delivered to students above the age of 14 in 21 schools, which were chosen by the Ministry of National Education in Adapazarı and Avcılar as highly affected by the quake. The questionnaire included the questions about the events, the students and their relative’s experiences after the quake. Results and Conclusion.- The effects of the quake on the state-trait anxiety test were assessed by logistic regression analysis. The injuries of the subjects (p<0.05, Exp(β):1.788, %95 C.I.:1.003-3.186) and their relatives (p<0.05, Exp(β):2.718, %95 C.I.:2.093-3.530), the damages on the houses (p<0.05, Exp(β):1.938, %95 C.I.:1.628-2.308) revealed the effects of state anxiety being positive. In accordance to that, the male (p<0.05, Exp(β):0.634, %95 C.I.: 0.538-0.747) students affected more at state anxiety. The damage on the houses (p<0.05, Exp(β):1.619, %95 C.I.: 1.261-2.078) and the treatment of the close relatives (p<0.05, Exp(β):2.997, %95 C.I.: 1.892-4.745) affects positively the trait anxiety. In addition, the male students (p<0.05, Exp(β):0.585, %95 C.I.: 0.467-0.732) seemed to develop less trait anxiety than the female students.